ORGANIZATIONAL COMMUNICATION STRATEGY FOR PUBLIC TRUST EXCELLENCE IN EDUCATION: FOCUS ON BUILDING TRUST - Jannah, Ulfa Qomariatul; Annisa', Tiara Nurul; Darina, Arini Naura; Holifah, Holifah; Rifa’i, Moh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In-depth interviews and documentation data analysis, this research found that transparency in finances, delivery of daily activities, publication of achievements, and policy announcements are the main components in Islamic boarding school communication strategies. Communication media such as official websites, social media and printed reports synergistically convey information to various audiences. The research results show that open and targeted communication not only increases public trust but also strengthens the image of Islamic boarding schools as professional, responsible and competitive institutions. This research contributes by offering a communication model relevant for other educational institutions, although there are limitations in the context and research methods that require further exploration.